Estudos teóricos e experimentais de complexos de cobre: propriedades espectroscópicas e atividade biológica - Oliveira, Herisson Faustino Santos de (Universidade Federal de São Carlos, 2020)
Cancer is the second leading cause of death in the world. The scientific community is mobilizing to study new compounds with cytotoxic potential and that can be used as molecular probes. However It is important to highlight that for every 100 thousand drug candidates synthesized, only one gets to the final clinical phase. One of the challenges of medicinal chemistry is to optimize the rate of success, increasing the efficiency of the process. In this context, polypyridic ligands act as good options, once when they are coordinated to a metallic center, their complexes can put together crucial structural features to promote their use as biological probes, due a visible bands, resulted of a charge transfer, and cytotoxic agents by intercalation with DNA. In this work, a theoretical investigation by DFT and TD-DFT of Cu II and Cu I complexes was carried out on their structural and spectroscopic properties. Cu II polypyridinics complexes were synthesized and characterized by UV-Vis, NMR, elemental analysis, fluorescence spectroscopy, conductivity and cyclic voltammetry. Data showed absorption and emission ranges above 400 nm, with quantum emission yield values compared to the literature standard [Ru(Bipy)3]2+. The IC50 values towards MDA-MB 231, MCF7 and PNT2 cell lines surpass the cytotoxicity of cisplatin. Ethidium bromide displacement assay showed that all compounds interacted to the DNA molecule and the molecular docking studies demonstrated the capacity of the compounds to act as DNA intercalating agents. Thus, the work indicated the potential of Cu II complexes as active biological agents, both with high cytotoxicity and luminescent properties.
Theoretical and experimental studies of copper complexes: spectroscopic properties and biological activity
Keywords: Quimica inorganica; Inorganic chemistry; CIENCIAS EXATAS E DA TERRA::QUIMICA